Essays on crude oil price differentials, oil price shocks, and the economy of Saudi Arabia - Albaqami, Modhi Hadyan (Kansas State University, 2023)
This dissertation incorporates three essays to examine the price differential between different-quality crude oils and the effect of oil price shocks on the Saudi economy. The first essay examined how price differences depending on crude oil quality have different regimes using a Markov switching model. The main difference between the two regimes is in the mean; the mean in the first regime shows no difference from zero, whereas the mean in the second regime is significantly positive, indicating consistency with a capacity constraint. The second essay compared two situations: one involving three shocks applying Kilian’s (2009) methodology versus one with only one shock to investigate whether considering a single shock is sufficient. Using three shocks showed a difference in how Saudi Arabia’s industrial production and consumer price index respond to oil supply and demand shocks, suggesting that it is not sufficient to consider only one shock. Finally, the third essay explored the reactions of Saudi Arabia’s stock market to oil market shocks using Kilian’s (2009) methodology and found that Saudi Arabia’s stock sectors react differently to oil price shocks. Saudi Arabia’s stock sectors reacted positively to oil-specific demand shocks but negatively to oil supply shocks; they showed no response to aggregate demand shocks.
Keywords: Oil price shock; Saudi Arabia economy; Price differential; Stock market